Ibn ‘Arabī on Divine Atemporality and Temporal Presentism - Lala, Ismail (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2024)
Muḥyī al-Dīn ibn ‘Arabī (d. 638/1240) is arguably the most influential philosophical mystic in Islam. He is also a presentist. This paper responds to the arguments of contemporary philosophers, Norman Kretzmann, William Lane Craig, Garrett DeWeese, and Alan Padgett, who argue that divine atemporality and temporal presentism are incompatible, through the temporal ontology of Ibn ‘Arabī. Ibn ‘Arabī asserts that all entities in the universe are loci of manifestation of God’s most beautiful Names. These divine Names constitute sensible reality. The principal response of Ibn ‘Arabī to the arguments of contemporary scholars is that the divine Names as they are manifested in the cosmos cannot be conflated with the divine Names as they are in themselves, which, in turn, cannot be conflated with God in His numinous essence. This allows him to simultaneously maintain the atemporality of God and temporal presentism.